A PRIMITIVE APPROACH ON REVIEW OF SIDDHA HERBS, HERBO-MINERAL FORMULATION EXHIBITING ANTIVIRAL ACTIVITY - B.SATHYA,; V.VELPANDIAN,; M.RAMANI,; M.PITCHIAH KUMAR., (International Journal of Pharma and Bio Sciences, 2014)
Viral disease is an issue of global and public health concern in this modern era. The traditional use of Siddha medicines serve as a milestone even in this scientific world in which a number of chemical combinative medicines are used. Several thousands of plant and herb species that are powerful antiviral agents have been studied. A wide variety of active phytochemicals, such as the flavanoids, terpenoids, lignans, sulphides, polyphenolics, coumarins, saponins, furyl compounds, alkaloids, polyenes, thiophenes, proteins and peptides are identified in herbs. Volatile oils of some commonly used kitchen herbs, tea of herbs and spices do possess antiviral activity. But it is still questionable about the pharmacopoeia of compounds in medicinal plants. These phytochemicals either inhibit viral DNA or RNA formation or viral replication. Antiviral drugs are said to be those drugs which effectively counteract the causative viruses. The present review is an initial step to consolidate the Siddha antiviral drugs present in the literature. This review illustrates that, there are countless potentially useful medicinal herbs for evaluation, exploitation and validation for therapeutic applications against morphologically, genetically and functionally different viral families such as Retroviridae, Hepadnaviridae and Herpesviridae. Several potential works have been done to list out the active principles, lateral research of selective viral diseases. The present review covered all the Siddha literatures from time immemorial till now.